Direct mechanical characterization of prostate tissue—a systematic review. Issue 2 (17th September 2018) - Kelly, Niall P.; Flood, Hugh D.; Hoey, David A.; Kiely, Patrick A.; Giri, Subhasis K.; Coffey, J. Calvin; Walsh, Michael T.
Abstract : Background: Direct mechanical characterization of tissue is the application of engineering techniques to biological tissue to ascertain stiffness or elasticity, which can change in response to disease states. A number of papers have been published on the application of these techniques to prostate tissue with a range of results reported. There is a marked variability in the results depending on testing techniques and disease state of the prostate tissue. We aimed to clarify the utility of direct mechanical characterization of prostate tissue in identifying disease states. Methods: A systematic review of the published literature regarding direct mechanical characterization of prostate tissue was undertaking according to PRISMA guidelines. Results: A variety of testing methods have been used, including compression, indentation, and tensile testing, as well as some indirect testing techniques, such as shear‐wave elastography. There is strong evidence of significant stiffness differences between cancerous and non‐cancerous prostate tissue, as well as correlations with prostate cancer stage. There is a correlation with increasing prostate stiffness and increasing lower urinary tract symptoms in patients with benign prostate hyperplasia. There is a wide variation in the testing methods and protocols used in the literature making direct comparison between papers difficult. Most studies utilise ex‐vivo or cadaveric tissue, while none incorporate in vivo testing. Conclusion: Direct mechanical assessment of prostate tissue permits a better understanding of the pathological and physiological changes that are occurring within the tissue. Further work is needed to include prospective and in vivo data to aid medical device design and investigate non‐surgical methods of managing prostate disease.